Тайм-менеджмент як інструмент оптимізації роботи менеджерів із закупівель - Чкан, А. С.; Чкан, Ірина Олександрівна; Chkan, Iryna; Рубан, О. (Дніпро : ПДАБА, 2021)
UA: У статті розглянуто сутність тайм-менеджменту як сучасної філософії організації роботи менеджерів. Доведено, що правильне застосування прийомів, технік, інструментів тайм-менеджменту є запорукою оптимізації роботи, досягнення цілей діяльності окремого працівника та підприємства в цілому найбільш ефективним способом. В роботі розроблено алгоритм тайм-менеджменту, відповідно до якого повинне здійснюватися формування плану робочого дня менеджера. Автором узагальнено інструменти, методи та технології тайм-менеджменту, що забезпечують оптимізацію роботи менеджерів на етапах планування, організації, мотивації та контролю діяльності. З метою оптимізації роботи менеджерів із закупівель в роботі запропоновано найбільш оптимальний варіант розподілу його функціональних задач впродовж робочого дня. /// EN: In the article the issues of optimizing the work of procurement managers are considered. Procurement is one of the most important processes in the activity of any enterprise. Timely and correctly organized process of supply of raw and materials ensures rhythmic and balanced operation of the enterprises. The absence of failures in the activity of enterprise is the result of properly organized work of managers, clearly defined plans for their work, lists of tasks and goals. Daily application of methods, techniques and technologies of time-management in the work of procurement managers is the main condition of their effectiveness. The author determined that today time-management is a philosophy of activity of managers. The provisions of time-management ensure the effective achievement of the goals of each individual manager and the enterprise as a whole. In the article the definition of «time-management», which are by various authors proposed, are generalized. On the base of these definitions the provisions of the functional purpose of time-management are defined. These provisions are: clear systematization and structuring of the list of tasks, reasonable goal setting, time rationing, coordination of tasks in time and space, time reservation, creation of favorable conditions for minimizing of time loss. In the article the algorithm of time-management is developed. This algorithm is a sequence of steps in each of which managers must make decisions about structuring tasks for the current period. The main questions of the algorithm are the priority and urgency of each task. The basis of the algorithm is a clear definition of the functional responsibilities and tasks of the procurement manager. At each phase of the manager's work (planning, organization, motivation, control) a set of different methods, tools and technologies of time-management can be used. The set of methods of time-management in the context of each function of the manager is clearly defined and generalized by the author. The practical value of the research is the proposition of the daily plan of the procurement manager in accordance with the provisions of time-management.
Time management as a tool of optimization of procurement managers’ work
Keywords: тайм-менеджмент; закупівлі; алгоритм; пріоритет; хронометраж; time-management; procurement; algorithm; priority; timing